Antigen presentation in retroviral vector-mediated gene transfer in vivo - Song, Elizabeth S. (The National Academy of Sciences of the USA, 1997)
We have examined mechanisms involved in gene transfer, protein expression, and antigen presentation after direct administration of retroviral vectors using a variety of antigen systems. We have identified transduced infiltrating cells at the injection site, and the majority of the infiltrating cells were of the monocyte/macrophage lineage. We found that the splenic dendritic cell fraction contained proviral DNA, expressed antigenic proteins, and was able to present antigens efficiently to the immune system. Furthermore, the dendritic cell fractions from retroviral vector-immunized mice were able to prime naive T cells in vitro, and adoptive transfer of in vitro-transduced dendritic cell fractions elicited antigen-specific cytotoxic T lymphocytes. These data suggest a role for dendritic cells in induction of immune responses elicited by retroviral vector-mediated gene transfer.